PERAN LEMBAGA FILANTROPI BAZNAS DALAM MENINGKATKAN SUMBER DAYA MANUSIA DI INDONESIA - Nurismalatri; Gustiana, Restia; Bayu, Yunus (JSE: Jurnal Sharia Economica, 2025)
Quality human resources (HR) are crucial assets for the progress of the nation. Islamic philanthropic institutions, such as the National Zakat Agency (BAZNAS), have great potential in contributing to improving the quality of HR. This study aims to analyze the role of BAZNAS Banten Province in efforts to improve HR in Indonesia through the programs it runs. The research method used is a case study with a qualitative approach, involving in-depth interviews with BAZNAS Banten Province administrators, program beneficiaries, and documentation studies related to HR empowerment programs. The results of the study indicate that BAZNAS Banten Province is active in implementing various programs oriented towards improving HR, including education, skills training, and economic empowerment. These programs have a positive impact on improving the knowledge, skills, and standard of living of mustahik, which in turn contributes to improving the quality of HR at the regional and national levels. This study recommends strengthening the synergy between BAZNAS, the government, and other civil society organizations to optimize the role of Islamic philanthropic institutions in HR development in Indonesia